Isolation And Characterization of Lactobacillus Species From Local Indonesian Cow’s Milk - Kandou, Abigail Sabrina; Sugata, Marcelia; Jo, Juandy (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2024)
Probiotics are a group of beneficial microorganisms that can improve the health of their host. Lactobacillus species are lactic acid bacteria that have great potential as probiotics, in which cow’s milk is a great source of lactic acid bacteria. In this study, Lactobacillus spp. were isolated from fresh local Indonesian cow’s milk. The methods used to characterize the Lactobacillus spp. were (i) biochemical tests including catalase, hemolytic and sugar fermentation tests; (ii) tolerance tests against salt (NaCl 2%, 4% and 6%), low pH (2, 3, 4, 5, 6 and 7) and temperature (7°C, 37°C and 45°C); and (iii) 16S rRNA sequencing. The isolation yielded 14 isolates matching the criteria of Lactobacillus spp. colony and cell (i.e., Gram positive rods that did not produce endospores and did not have a waxy layer covering its cell wall). Based on subsequent biochemical tests, 5 isolates were suspected as potential probiotic Lactobacillus spp. The 16S rRNA sequencing revealed that the isolate L was Limosilactobacillus fermentum. In conclusion, this study demonstrated that local cow’s milk could be used to isolate Lactobacillus spp.